ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA PERUSAHAAN (Studi Empiris Perusahaan Sub Sektor Pakan Ternak yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Parulian Simanjuntak; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
The aim of this research was to determine the influence of the implementation of good coporate governance on company’s performance. This research used board of directors, proportion of independent board of commisioners, and audit comittee as the indicators. The population were all animal feed sub sector companies listed on Indonesia Stock Exchange (BEI), the sampling method used was purposive sampling. Based on the result of the selection, there are 4 samples of selected companiess which means 20 samples of financial report. This research used secondary data in the form of financial statement (annual report) of company listed on the Indonesia Stock Exchange (BEI). The method used in this research was quantitative descriptive method by using some calculation analysis, such as classic assumption test, correlation coefficient analysis, significance test, coefficient of determination analysis, and linear regression analysis with the help of software SPSS. The result showed that the correlation (r) of each indicator were 0.310, 0.045, and 0.218, which means there was a low correlation between board of directors, proportion of independent board of commisioners, and audit comittee toward return on asset (ROA) where simultaneously GCG has no significant effect on company’s performance.